2013
DOI: 10.3389/fpsyg.2013.00791
|View full text |Cite
|
Sign up to set email alerts
|

A game theoretic framework for incentive-based models of intrinsic motivation in artificial systems

Abstract: An emerging body of research is focusing on understanding and building artificial systems that can achieve open-ended development influenced by intrinsic motivations. In particular, research in robotics and machine learning is yielding systems and algorithms with increasing capacity for self-directed learning and autonomy. Traditional software architectures and algorithms are being augmented with intrinsic motivations to drive cumulative acquisition of knowledge and skills. Intrinsic motivations have recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The remainder of the algorithm proceeds as follows: Each agent in the swarm is initialized with an OMI, Ω j (line 1) [30]. At each time step, each agent senses the local state of its environment (line 4), including the features described above for position, velocity and neighbors within different ranges.…”
Section: Crowds Of Motivated Agentsmentioning
confidence: 99%
“…The remainder of the algorithm proceeds as follows: Each agent in the swarm is initialized with an OMI, Ω j (line 1) [30]. At each time step, each agent senses the local state of its environment (line 4), including the features described above for position, velocity and neighbors within different ranges.…”
Section: Crowds Of Motivated Agentsmentioning
confidence: 99%
“…However, a number of studies have shown that decision makers in many real situations do not adhere to these assumptions [90]. This has led to an increasing recognition that it is necessary to model players in greater detail, considering their behavioural characteristics including intent, objectives, strategies [5] and motives [6]. A few different branches have emerged in game theory literature that specifically focus on bounding the rationality assumption.…”
Section: Alternative Models In Game Theorymentioning
confidence: 99%
“…These games are analysed to establish their equilibrium points and suggest beneficial strategies for players. However, it is increasingly recognised that it is necessary to model players in greater detail, including their intent, objectives and strategies [5] and their motives [6]. This paper presents a taxonomy of games that map to information warfare and cyber crime problems, as a precursor to future research on decision-making in such scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, differences in implicit motives have also been linked to differences in preferences for explicit incentives such as money, points or "payoff" in a game [2][3][4][5] or during other kinds of strategic interactions [6]. Computational motivation has emerged as an area of interest among artificial intelligence [7,8] and robotics [9][10][11] researchers, as a mechanism for enabling autonomous mental development [12] or modelling human-like decision-making [8,13]. This paper falls in this latter category.…”
Section: Open Accessmentioning
confidence: 99%
“…Later work simplifies this kind of model for game-theoretic settings using the concept of an optimally motivating incentive (OMI) [8,23]. The OMI is the incentive value that maximizes a motivation curve.…”
Section: Assumptions and Related Workmentioning
confidence: 99%